2022
DOI: 10.1111/acel.13683
|View full text |Cite
|
Sign up to set email alerts
|

Soluble guanylate cyclase activator BAY 54–6544 improves vasomotor function and survival in an accelerated ageing mouse model

Abstract: DNA damage is a causative factor in ageing of the vasculature and other organs. One of the most important vascular ageing features is reduced nitric oxide (NO)soluble guanylate cyclase (sGC)-cyclic guanosine monophosphate (cGMP) signaling. We hypothesized that the restoration of NO-sGC-cGMP signaling with an sGC activator (BAY 54-6544) may have beneficial effects on vascular ageing and premature death in DNA repair-defective mice undergoing accelerated ageing. Eight weeks of treatment with a non-pressor dosage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…NO deficiency related to older age could also result from increased oxidative stress leading to a dysfunctional NOS system [52]. Downstream signaling, namely, soluble guanyl cyclase (sGC), or other members of the cascade (such as PDE5) could also malfunction in older age [53][54][55][56][57][58]. We consider that this might be the most likely explanation for our findings, but this hypothesis requires further experimental evidence to be confirmed.…”
Section: Baseline Nitritementioning
confidence: 84%
“…NO deficiency related to older age could also result from increased oxidative stress leading to a dysfunctional NOS system [52]. Downstream signaling, namely, soluble guanyl cyclase (sGC), or other members of the cascade (such as PDE5) could also malfunction in older age [53][54][55][56][57][58]. We consider that this might be the most likely explanation for our findings, but this hypothesis requires further experimental evidence to be confirmed.…”
Section: Baseline Nitritementioning
confidence: 84%
“…The molecular mechanisms behind the biphasic effect of HO on the expression of these genes in HDLECs are unclear and require further study. In addition to reflecting the oxidative stress status of a cell, HO1 and NQO1 have several vasculoprotective effects [ 83 , 84 , 85 , 86 ]. Therefore, our finding of increased HO1 and NQO1 expression in HDLECs suggests that these cells are under oxidative stress following HO exposure, and they upregulate HO1 and NQO1 expression as an adaptive response to mitigate the effects of HO.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming the above, studies in animal models have revealed that vascular aging is earlier the more some of the mechanisms that regulate the response to vasomodulating substances are altered: in knockout animals for some genes involved in nuclear DNA damage repair mechanisms of vascular smooth muscle cells, nonatherosclerotic decay was seen due to altered endothelial responses [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 94%